2020
DOI: 10.1080/23748834.2020.1833281
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between housing created through Permitted Development Rights and health: a systematic review

Abstract: Permitted Development Rights are a regulatory mechanism in the English planning system where the use of a building can be changed bypassing the standard planning process. Other countries have similar arrangements. In England, no assessment of the health impacts has been completed. This systematic review provides the first overview of the health and wellbeing impacts of housing created through Permitted Development Rights. 1,999 literature items were identified from a structured search of 14 databases and manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…This legislative instrument essentially allows a host of permitted construction works to be undertaken while circumventing the need for planning permission (House of Commons, 2019). However, the foremost benefit of PD rights (Marsh et al , 2020) is the ability to facilitate the conversion of commercial and industrial properties into residential properties whilst bypassing the conventional planning permission process. The implementation of PD rights saw a vast increase in net housing production which was derived directly from the preceding conversion works (MHCLG, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This legislative instrument essentially allows a host of permitted construction works to be undertaken while circumventing the need for planning permission (House of Commons, 2019). However, the foremost benefit of PD rights (Marsh et al , 2020) is the ability to facilitate the conversion of commercial and industrial properties into residential properties whilst bypassing the conventional planning permission process. The implementation of PD rights saw a vast increase in net housing production which was derived directly from the preceding conversion works (MHCLG, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As pressures on land in increase, and developers attempt to cram more homes on available sites than ever before, it is possible there will be demands to revise the NDSS downwards to normalise smaller housing, both from housebuilders but also planning authorities keen to deliver on housing targets (Wiles, 2020). But against this, mounting evidence of the negative health and well-being impacts of reduced space (Marsh et al, 2020;Preece et al, 2023;Kearns, 2022) presents a case for rigid enforcement of higher standards. The future inclusion of the NDSS in National Development Management Policies may well ensure more consistency in the "Substandard" English housing application of space standards across different local authorities, but this paper suggests there remains a need to better document the vagaries of Appeal processes so that both planners and housebuilders are more aware of the forms of discretion being exercised in judgements of housing adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…The location of several notable conversions alongside major highways has raised particular anxieties about air pollution (Marsh et al, 2022). London regularly experiences levels of NO 2 exceeding EU-recommended limits, with pronounced inequalities present: Fecht et al (2016) found NO 2 concentrations 7.8 μg/m 3 higher in the most deprived neighbourhoods compared with the least deprived.…”
Section: Pollutionmentioning
confidence: 99%